A Simple Interference and Power-based Direction of Arrival Measuring System for Modern Communication - Vu, Nga; Le, Thinh; Dinh, Minh; Le, Minh Thuy (Applied Computational Electromagnetics Society Journal (ACES), 2023)
In this paper, we present a system specialized for measuring the direction-of-arrival (DoA) of electromagnetic waves with noticeable simplicity. Unlike common methods, which are based heavily on complex computation and signal processing, our proposed system is considerably simpler, both in terms of design and operating theory. Our design consists of two directional antennas for collecting incident waves, a system of Wilkinson power combiners and dividers in which the waves collected by the antennas interfere, a result-processing block consisting of power amplifiers, rectifiers, and a microcontroller unit that respectively converts the interferometric radio-frequency (RF) signal into direct-current (DC) signal, measures its corresponding power before calculating the incident angle solely based on a simple trigonometric equation. The system yields a high accuracy of less than 7.5o with the incident angle ranging from −60o to 60o.